2015
DOI: 10.4103/0973-1482.138098
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of particle penetration of smokeless tobacco forms using egg shell membrane as a substrate

Abstract: The degree of diffusion gradually increased with a decrease in the particle size establishing an inverse relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There are several hypotheses brought in literature regarding possible connection between smoking habits and oral Candida: mucosal changes effecting the colonization of candida [9], pro-candidal factors found in tobacco [13], the correlation between acidification of saliva (caused in part by smoking) and carriage state of candida [2] There exists a strong relationship between the tobacco particle size and tobacco related cancer and potentially malignant disorders. Over the past decades, numerous studies have been done to analyze the effect of chemical composition of these products on oral mucosa [53]. In a study done by Naziya K.B et al among dental students revealed that the mean knowledge score among males and females was 24 and 23.9, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are several hypotheses brought in literature regarding possible connection between smoking habits and oral Candida: mucosal changes effecting the colonization of candida [9], pro-candidal factors found in tobacco [13], the correlation between acidification of saliva (caused in part by smoking) and carriage state of candida [2] There exists a strong relationship between the tobacco particle size and tobacco related cancer and potentially malignant disorders. Over the past decades, numerous studies have been done to analyze the effect of chemical composition of these products on oral mucosa [53]. In a study done by Naziya K.B et al among dental students revealed that the mean knowledge score among males and females was 24 and 23.9, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study can be correlated to several studies wherein the prevalence of potentially malignant disorders and oral squamous cell carcinoma were assessed in smokeless tobacco users [ 18 ]. A review of literature on various smokeless tobacco products in potentially malignant and malignant disorders demonstrated a greater prevalence of OSMF in gutka and mawa users and leukoplakia, erythroplakia and malignancies in tobacco leaf chewers [ 19 ] This could be due to the release of nitrosamines and other carcinogens from the tobacco leaf which could have a synergistic action on the particle size of the tobacco products [ 20 ]. Though khaini, having the smallest particle size has greatest association with OSMF compared with other forms, the number of studies done with khaini is comparatively less probably due to the late emergence of these products in 1990's.…”
Section: Discussionmentioning
confidence: 99%